Divine Action and Quantum Theory - Tracy, Thomas F. (Zygon, 2000)
Recent articles by Nicholas Saunders, Carl Helrich, and Jeffrey Koperski raise important questions about attempts to make use of quantum mechanics in giving an account of particular divine action in the world. In response, I make two principal points. First, some of the most pointed theological criticisms lose their force if we attend with sufficient care to the limited aims of proposals about divine action at points of quantum indetermination. Second, given the current state of knowledge, it remains an open option to make theological use of an indeterministic interpretation of quantum mechanics. Any such proposal, however, will be an exploratory hypothesis offered in the face of deep uncertainties regarding the measurement problem and the presence in natural systems of amplifiers for quantum effects.